Prevalence and correlates of suicidal ideation with dermatological morbidities - Bharati, Dharmvir Ranjan; Kumari, Seema; Jaykar, Kranti Chand; Kumar, Ajay; Choudhary, Sanjay Kumar; Rajak, Birendra Kumar (International Journal Of Community Medicine And Public Health, 2018)
Background: The dermatologic consultation might be a precious opportunity to recognize and treat depression associated with suicidal ideation in these patients. This study aimed to find the prevalence of suicidal ideation among patients with dermatologic conditions, and identifying demographic variables of suicidal ideation. Methods: This institution based cross-sectional study was conducted during February to March 2017, at dermatological out-patients department of the teaching hospital Indira Gandhi Institute of Medical Sciences (IGIMS), Patna, India. Results: Of 396 adults with skin disease 272 (68.69%) were male. Prevalence of suicidal tendency was significantly more among young adults and higher in females (38.7%) than males (1.5%). In males, suicidal tendency was in patients suffering from tinea infection while among females, significantly more observed among patients suffering from tinea 38.71%, psoriasis 22.58% and chronic idiopathic urticaria 16.13%. The risk of suicidal tendency in males were significantly higher among 18–20 years, unemployed, belongs to smaller family, having lower body mass index and suffering from depression. While in females, suicidal tendency was significantly higher among early adulthood, not or lower education, unemployed, no personal income and vegetarian, belongs to large family, no family support, having lower body mass index and suffering from depression as well as suffering from some other medical comorbidity in addition to skin diseases. Conclusions: Risk correlates of suicidal ideation with skin diseases were early adulthood, lower education, unemployment with no personal income, vegetarian diet, large family, no family support, lower body mass index and suffering from depression and comorbidities.